Formation of the PNAIC in geometry and the educational trajectory of the literacy teachers - Barbosa, Aline Pereira Ramirez [UNESP]; Cortela, Beatriz Salemme Corrêa [UNESP] (FapUNIFESP (SciELO), 2018)
In this work, we present the educational trajectory of five literacy teachers regarding the learning in Geometry and how, after they participated in the continuous formation of these concepts based on the National Pact of Literacy in the Right Age (PNAIC), they elaborated their teaching strategies and evaluated this course. This work, which is of a qualitative character, had semi-structured interviews and field notes elaborated during class observations as instruments of data collection. For the analysis, we used methodologies resulting from the French Line of the Discourse Analysis aiming to understand the production conditions in which these subjects are situated. Our results showed that there was a conceptual gap in the formation of these participants, and the discourses indicated that they were influenced by the abandonment or minimization of geometric concepts, affecting how they currently understand and elaborate their teaching work in relation to this topic.
Formação do PNAIC em Geometria e a Trajetória Educacional dos Professores Alfabetizadores
Keywords: Educational trajectory; Geometry Teaching; Literacy Cycle; PNAIC